Cross-Sectional Research on the Predictors of Physical Fitness of Athletes in Universities in Iraq - Ali Salman; Murtada Sultan Al-Issa; Taha Al Hiali; Abdul Razzaq Jaber Al Majidi; Zaid Hilal Abed Alqiraishi; Ali Falah Mohamed; Hussam Abdali Abdulridui; Maher Mohamed Al-Ameri; Mortada Kareem Sabi AlTalb (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The focus of this study was the physical fitness of athletes in Iraq. The objective of the present study was to assess the influence of four variables—coaches' positive behaviour, sports activities, mental health monitoring, and sports training—on the physical fitness of athletes in Iraq. The study aimed to gather quantitative data using a carefully constructed questionnaire. The research focused on the athletes enrolled in universities across Iraq. A total of 1,000 questionnaires were distributed to respondents in a cross-sectional design, from which 850 responses were selected for data analysis. The relationships in this research were examined using statistical methods such as confirmatory factor analysis and structural equation modelling, implemented through the R Package. The study revealed that the positive behaviour of coaches, engagement in sports activities, monitoring of mental health, and sports training all play a crucial role in enhancing the physical fitness of athletes in Iraq. This research is unique and adds valuable insights to the existing literature by addressing areas of knowledge that have not been previously explored. In order to enhance the physical fitness of athletes, it is imperative for policymakers to ensure that coaches are equipped with the necessary tools. This includes fostering positive behaviour, organising sports activities, monitoring mental health, and providing comprehensive sports training.